Overview of bergamot leaves extract (Citrus bergamia) effect on the RedOx/Inflammatory scenario in obesity target organs in an animal model of metabolic syndrome - Siqueira, Juliana Silva [UNESP]; Nakandakare-Maia, Erika Tiemi [UNESP]; Vieira, Taynara Aparecida [UNESP]; Palacio, Thiago Luiz Novaga [UNESP]; Belin, Matheus Antônio Filiol [UNESP]; Baron, Giovanna; Bazan, Silmeia Garcia Zanati [UNESP]; Ferron, Artur Junio Togneri; Aldini, Giancarlo; Francisqueti-Ferron, Fabiane Valentini [UNESP]; Corrêa, Camila Renata [UNESP] (Elsevier, 2024)
Bergamot (Citrus bergamia) is a fruit with anti-inflammatory and antioxidant properties that contains similar bioactive composition to its leaf, evidencing its therapeutic potential in the treatment of chronic diseases. The aim was to evaluate the treatment effect of bergamot leaf extract (BLE) on the redox/inflammatory scenario in different organs of obese rats with metabolic syndrome. After detection of metabolic syndrome, male Wistar rats were allocated (n = 10/group) for the treatment with BLE by gavage (50 mg/kg): Control, Control+BLE, High Sugar fat (HSF), and HSF+BLE. Evaluations included: metabolic-nutritional profile; tissues function and redox/inflammatory parameters. The HSF group presented metabolic syndrome, cardiac, hepatic and renal dysfunction; inflammation; and oxidative stress. BLE decreased oxidative stress and inflammation levels in adipose tissue, heart, liver and kidneys, as well as decreased levels of triglycerides, insulin and insulin resistance. BLE act in all target organs of obesity, improving the redox/inflammatory scenario in a diet-induced metabolic syndrome.
Keywords: Bioactive compound; Inflammation; Oxidative stress; Western diet